High sensitivity pH sensor based on porous silicon (PSi) extended gate field-effect transistor - Al-Hardan, N.H.; Hamid, M.A.A.; Ahmed, N.M.; Jalar, A.; Shamsudin, R.; Othman, N.K.; Keng, L.K.; Chiu, W.S.; Al-Rawi, H.N. (MDPI, 2016)
In this study, porous silicon (PSi) was prepared and tested as an extended gate field-effect transistor (EGFET) for pH sensing. The prepared PSi has pore sizes in the range of 500 to 750 nm with a depth of approximately 42 µm. The results of testing PSi for hydrogen ion sensing in different pH buffer solutions reveal that the PSi has a sensitivity value of 66 mV/pH that is considered a super Nernstian value. The sensor considers stability to be in the pH range of 2 to 12. The hysteresis values of the prepared PSi sensor were approximately 8.2 and 10.5 mV in the low and high pH loop, respectively. The result of this study reveals a promising application of PSi in the field for detecting hydrogen ions in different solutions.